A ferry making waves: A demonstration project 'doing' institutional work in a greening maritime industry. Issue 1 (1st January 2019) - Sjøtun, Svein Gunnar
ABSTRACT: The objective of the article is to show how the demonstration project and battery ferry Ampere has contributed to a greening of public ferry procurement in Norway. Building on theories on demonstration projects in transition studies and institutional work, the author argues for a more integrated focus than hitherto on the dynamic interplay of materiality, organization, and discourse in demonstration projects, and how the agency of actor networks and the materiality connected to demonstration projects can affect institutional change accompanying transition processes. This is done by conceptualizing Ampere as a 'performing project': a complex of discursive and organizational strategies of framing and lobbying deployed by the actor networks connected to it and its materiality. Methodically, the author draws on semi-structured interviews and document analysis. The results suggest that Ampere's 'performance' has contributed to changes in national and regional ferry procurement practices and been vital for an emerging maritime battery niche.